Simulium (Nevermannia) chomthongense, a new species of black fly (Diptera: Simuliidae) from Chiang Mai, Thailand - H. Takaoka (2018)
Simulium (Nevermannia) chomthongense sp. nov. is described from female, male, pupal and larval specimens collected from Doi Inthanon National Park and Doi Phahompok National Park, Chiang Mai, Thailand. This new species, first reported as S. (Eusimulium) sp. A, and later regarded as S. (N.) caudisclerum Takaoka & Davies, described from peninsular Malaysia, is distinguished from S. (N.) caudisclerum in the male by the number of enlarged upper-eye facets and the relative size of the hind basitarsus against the hind tibia and femur, and in the pupa by the relative length of the stalks of paired filaments against the common basal stalk and the color of the dorsal surface of abdominal segments 1-3 (or 4). Taxonomic and molecular notes are provided to separate this new species from four other known species of the vernum species-group, which share an accessory sclerite on the larval abdomen, a rare characteristic in this species-group.